A Reconstruction of Proto-Philippine Phonemes and Morphemes - Paz, Consuelo J. (The Archive; Vol 3 (1981): Publication Three: A Reconstruction of Proto-Philippine Phonemes and Morphemes, 2025)
The objective of this study is the reconstruction of Proto-Philippine phonemes and morphemes using the comparative method. In undertaking this task, I hope to verify the relationship that holds between the languages found in the Philippines, and to test the workability of the comparative method for the Philippine languages which have no historical texts earlier than the 16th century. The specific results of this study are the reconstruction of the Proto-Philippine phonemes and a dictionary of proto-phonemes. This study therefore deals with the phonologic system and part of the lexicon of the posited Proto-Philippine language. As Hoenigswald (1950: 357) says, attempting to reconstruct the earlier language by means of the comparative method is “essentially a problem in phonemics.” The establishment of the sound system of the posited parent language is generally given precedence over its other systems1 since the evidence for it is more readily systematized and more readily fulfills the principle of total accountability. Reconstructing the other systems of the earlier language would mean a much more comprehensive work entailing more time and diverse data which I am not in a position to deal with at present. Thus, morphologic and syntactic comparison and reconstruction will have to be treated in a sequel to this present study. The semantic system likewise deserves a separate treatment.